Disputes about Jan Hus and Czech Catholic Historiography in Late 19th and Early 20th Century - Nodl, Martin (Dějiny – teorie – kritika, 2013)
This study deals with issues related to the perception of Jan Hus from a confessional point of view in late 19th and early 20th century. It presents an analysis of texts by Antonín Lenz and Jan Sedlák, both Catholic historians, in contraposition with liberal and Protestant historiography represented by Václav Flajšhans, Václav Novotný, and Vlastimil Kybal. The author concludes that in some aspects of the historiographic discourse, a national approach to Hus and his work was more important than positions defined purely along confessional lines. This was most apparent in the attitude of Czech historians to Johann Loserth’s claims and in their attempt to make a clear distinction between Hus’s reformism and heretical positions of the revolutionary Hussites.